Achieving Equity in the Reach of Smoking Cessation Services Within the NCI Cancer Moonshot-Funded Cancer Center Cessation Initiative (Mary Ann Liebert, 2021)
Background: Ensuring equitable access to smoking cessation services for cancer patients is necessary to avoid increasing disparities in tobacco use and cancer outcomes. In 2017, the Cancer Center Cessation Initiative (C3I) funded National Cancer Institute (NCI)-designated Cancer Centers to integrate evidence-based smoking cessation programs into cancer care. We describe the progress of C3I Cancer Centers in expanding the reach of cessation services across cancer populations. Methods: Cancer centers (n=17) reported on program characteristics and reach (the proportion of smokers receiving evidence-based cessation treatment) for two 6-month periods. Reach was calculated overall and by patient gender, race, ethnicity, and age. Results: Average reach increased from 18.5% to 25.6% over 1 year. Reach increased for all racial/ethnic groups, and in particular for American Indian/Alaska Native (6.6?24.7%), Asian/Native Hawaiian/Pacific Islander (7.3?19.4%), and black (18.8?25.9%) smokers. Smaller gains in reach were observed among Hispanic smokers (19.0?22.8%), but these were similar to gains among non-Hispanic smokers (18.9?23.9%). By age group, smokers aged 18?24 years (6.6?14.5%) and >65 years (16.1?24.5%) saw the greatest increases in reach. Conclusion: C3I Cancer Centers achieved gains in providing smoking cessation services to cancer patients who smoke, thereby reducing disparities that had existed across important subgroups. Taking a population-based approach to integrating tobacco treatment into cancer care has potential to increase reach equity. Implementation strategies including targeted and proactive outreach to patients and interventions to increase providers' adoption of evidence-based smoking cessation treatment may advance reach even further.